Rubber wood industry - De Silva K G K (Bulletin of the Rubber Research Institute of Sri Lanka, 1997)
There is no doubt that rubber wood can be labelled as the Wood for the future. The recent government ban on felling jak, breadfruit and even coconut trees will aggravate the current position of a severe shortage of timber. Therefore rubber wood will become more and more prominent in the future. Although rubber wood can be considered as sustainable, renewable and eco-friendly wood resource to substitute presently available other good quality timber varieties there is a negative product image basically due to unawareness and confusion about treated and untreated rubber wood. However we must accept the fact that the quality of all treated wood is not excellent. Rubber wood is a semi hard wood, light colour wood with reasonably good strength properties. It also has good gluing and sanding properties. Rubber wood can be drilled or bored without any difficulty. Therefore rubber wood has an immense potential as a valuable timber which could play a vital role in economic and industrial development in the country and the shortage of hard wood in furniture consumption and wood in buildings and wood works will further boost the demand.
Keywords: Rubberwood industry; Rubberwood treatment